Association of Preoperative Coagulability With Incidence and Extent of Portal Vein Tumor Thrombus and Survival Outcomes in Hepatocellular Carcinoma After Hepatectomy: A Large-Scale, Multicenter Study - Zhang, Xiu-Ping; Zhou, Teng-Fei; Feng, Jin-Kai; Sun, Zi-Yang; Zhen, Zuo-Jun; Zhou, Dong; Zhang, Fan; Hu, Yi-Ren; Zhong, Cheng-Qian; Chen, Zhen-Hua; Chai, Zong-Tao; Wang, Kang; et al. (Frontiers in Oncology, 2021)
Background: Occurrence of portal vein tumor thrombus (PVTT) worsens the outcomes of hepatocellular carcinoma (HCC) and imparts high economic burden on society. Patients with high risks of having hypercoagulation are more likely to experience thrombosis. Herein, we examined how preoperative International Normalized Ratio (INR) was related to the incidence and extent of PVTT, and associated with survival outcomes in HCC patients following R0 liver resection (LR). Methods: Patients with HCC and PVTT were enrolled from six major hospitals in China. The overall survival (OS) and recurrence-free survival (RFS) rates of individuals with different INR levels were assessed with Cox regression analysis as well as Kaplan-Meier method. Results: HCC patients in the Low INR group had a significantly higher incidence of PVTT and more extensive PVTT than the Normal and High INR groups (P<0.005). Of the 592 HCC subjects who had types I/II PVTT following R0 LR, there were 106 (17.9%), 342 (57.8%) and 144 (24.3%) patients in the High, Normal and Low INR groups, respectively. RFS and OS rates were markedly worse in patients in the Low INR group relative to those in the Normal and High INR groups (median RFS, 4.87 versus 10.77 versus 11.40 months, P<0.001; median OS, 6.30 versus 11.83 versus 12.67 months, P<0.001). Conclusion: Preoperative INR influenced the incidence and extent of PVTT in HCC. Particularly, patients with HCC and PVTT in the Low INR group had worse postoperative prognosis relative to the High and Normal INR groups.